The internet addiction and the impact on the cognitive, psychological and social side of people’s personality with disabilities - Vouglanis, Taxiarchis; Drigas, Athanasios (Technium Social Sciences Journal, 2022)
Today, Information and Communication Technologies (ICT) prevail in all areas of society, while their consolidation has brought about significant changes. Children and young people come into contact with them every day and the skills and knowledge they have acquired empirically are many. Nowadays, new technologies are considered very essential and anyone who does not have skills in this field is considered as “illiterate” as was used to be in the past for those who did not know writing and reading. Their establishment at all levels makes the use of new technologies indispensable to everyone because without such knowledge people cannot participate in key areas and processes that define them both as people and as citizens. New technologies are increasingly developing and, combined with the globalization and the economic changes that are taking place, even more intense changes are expected to occur that will have a critical impact on all people in the future, regardless of gender.